2022
DOI: 10.3168/jds.2021-21032
|View full text |Cite
|
Sign up to set email alerts
|

Transferring a large data library of fresh total mixed rations from a benchtop to 2 portable near-infrared spectrometers for on-farm real-time decisions

Abstract: This study was carried out using a spectral database consisting of 394 samples of fresh total mixed ration (TMR) from dairy farms located at Northern Spain. Cloning sets of different size and structure were evaluated for the transfer of the large TMR spectral database obtained on a Foss NIRSystems monochromator to 2 different portable near-infrared devices: one diode array instrument and another based on linear variable filters. The cloning matrix that produced the best matching between instruments was then us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Beside the marked computation differences, both methods seem fitted to transfer calibration from a monochromator like LAB and a diode array sensor, which would make it easy and effective in using older calibration database for diode array instruments. Applying the same instruments involved in this study (FOSS NIRSystems 6500 & Aurora NIR (GraiNit S.R.L, IT), Pérez-Marín et al 6 successfully transferred the calibration from NIR labbench instrument to portables for a dataset of TMR forage using SW standardization algorithm, which didn’t perform very well in our study with alfalfa samples, although it was satisfatory with grasses. The key point again seems to be the lower spectral correlation between LAB and the portable instruments using alfalfa samples.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Beside the marked computation differences, both methods seem fitted to transfer calibration from a monochromator like LAB and a diode array sensor, which would make it easy and effective in using older calibration database for diode array instruments. Applying the same instruments involved in this study (FOSS NIRSystems 6500 & Aurora NIR (GraiNit S.R.L, IT), Pérez-Marín et al 6 successfully transferred the calibration from NIR labbench instrument to portables for a dataset of TMR forage using SW standardization algorithm, which didn’t perform very well in our study with alfalfa samples, although it was satisfatory with grasses. The key point again seems to be the lower spectral correlation between LAB and the portable instruments using alfalfa samples.…”
Section: Resultsmentioning
confidence: 93%
“…These samples were selected because the average and range of chemical composition of this study represented the composition of calibration and validation sets (data not shown). The number of samples was larger than that recommended by Shenk and Westerhaus 24 and Perez Marin et al, 6 which should ensure robust calibration transfer even in the presence of potential spectra variability within samples, that could result from the different sample presentations of the instruments used in this study.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations